2019
DOI: 10.1101/522839
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plant seeds are primed by herbivore-induced plant volatiles

Abstract: 23Mature plants can detect and respond to herbivore-induced plant volatiles (HIPVs) by priming or 24 directly activating defenses against future herbivores. Whether other plant life stages can respond 25 to HIPVs in similar manners is poorly understood. For example, seeds are known to respond to a 26 variety of environment cues that are essential for proper germination timing and survival. Seeds 27 may also be exposed to HIPVs prior to germination, and such exposure may affect the growth, 28 development, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…Indole can also interact with ( Z )‐3‐hexenyl acetate to produce stronger and more specific defence responses and herbivore resistance (Hu et al, 2019). Recent work found that exposure of Arabidopsis thaliana and Medicago truncatula seeds to indole reduces subsequent herbivore performance, suggesting that indole may also promote herbivore resistance in dicotyledonous plants (Maurya, Pazouki, & Frost, 2019). While it has been reported that herbivore attack elicits indole emission in poplar, tea and apple ( Malus × domestica ) plants (Cai, Sun, Dong, Wang, & Chen, 2013; Frost et al, 2007; Giacomuzzi et al, 2016), whether indole can also increase herbivore resistance in woody plants is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Indole can also interact with ( Z )‐3‐hexenyl acetate to produce stronger and more specific defence responses and herbivore resistance (Hu et al, 2019). Recent work found that exposure of Arabidopsis thaliana and Medicago truncatula seeds to indole reduces subsequent herbivore performance, suggesting that indole may also promote herbivore resistance in dicotyledonous plants (Maurya, Pazouki, & Frost, 2019). While it has been reported that herbivore attack elicits indole emission in poplar, tea and apple ( Malus × domestica ) plants (Cai, Sun, Dong, Wang, & Chen, 2013; Frost et al, 2007; Giacomuzzi et al, 2016), whether indole can also increase herbivore resistance in woody plants is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, using M. euphoribae, significant lower numbers of newborn nymphs and lower number of settled individuals, with lower weight, were recorded on tomato plants when primed by β-ocimene (Cascone et al, 2015). More recently, Maurya et al (2019) reported a reduced fecundity of pea aphid on barrel medic plants upon their exposure to indole.…”
Section: Associational Resistance Of Cis-jasmone Primed Plantsmentioning
confidence: 90%
“…Indole is a derivative of the shikimate acid pathway. Exposure to indole primes plant defenses against herbivores in both monocotyledonous and dicotyledonous plants (Maurya et al ., 2019; Ye et al ., 2019). Terpenes are the largest and most structurally diverse class of volatiles.…”
Section: Volatiles As Cues In Indicators Of Herbivory Challengementioning
confidence: 99%